Network security :private communication in a public world - Kaufman, Charlie (Pearson, 2017)
The first edition of Network Security received critical acclaim for its lucid and witty explanations of the inner workings of network security protocols. Honored by Network Magazine as one of the top 10 most useful networking books, it is now fully updated for the latest standards and technologies.